العجــــــائبية في روايــــة أنتيخريستوس لــأحمد خالد مصطفى - جهينة زوقاري (My University, 2024)
Abstract: This study includes the theorization of the term "wonderful" and its conceptualization, as well as highlighting the most important interdisciplinary fields related to it, including the marvelous, the strange, and the supernatural. It also critically examines this term in the Western and Arab contexts, showcasing its presence in Western and Arab literature, starting with the West as it is a Western term. In the West, its presence is highlighted in foreign blogs, blogs from the Middle Ages, and up to the blogs of the Renaissance. As for the Arabs, its presence is highlighted in various sources, including popular heritage, Sufism, and the novel, while addressing its key conditions and then applying them to the novel "Antichristos" by Ahmed Khaled Mustafa, highlighting the manifestations of wonder in it, starting from the title through the characters, time, place, and finally language ------------------ الملخص: تحتوي هذه الدراسة على بداية التنظير لمصطلح العجائبية و التأصيل له وكذا ابراز أهم الحقول المعرفية المتداخلة معه منها العجيب و الغريب و الخارق كذلك التناول النقدي لهذا المصطلح عند الغرب و العرب وابراز تواجدها في الأدب الغربي و الأدب العربي بدء بالغرب لأنه مصطلح غربي أما عند الغرب فأبرزت تواجدها في المدونات الأجنبية و مدونات العصور الوسطي وصولا الى مدونات عصر النهضة أما عند العرب فأبرزت تواجدها في روافد كثيرة منها التراث الشعبي و الصوفية و الرواية مع التطرق الى أبرز شروطها ثم التطبيق على رواية أنتيخريستوس لأحمد خالد مصطفى وابراز تجليات العجائبية فيها بدء من العنوان مرورا الى الشخصيات ثم الزمان و المكان وصولا الى اللغة . ------------------- Rèsumè: Cette étude commence par la théorisation du terme "l'étrange" et sa conceptualisation, en mettant en lumière les domaines de connaissance interconnectés tels que e merveilleux, l'étrange et le surnaturel. Elle aborde également une analyse critique de ce terme chez les Occidentaux et les Arabes, en soulignant sa présence dans la littérature occidentale et arabe, en commençant par l'Occident car c'est un terme occidental. Du côté occidental, sa présence est mise en avant dans les blogs étrangers, les blogs du Moyen Âge jusqu'aux blogs de la Renaissance. Du côté arabe, sa présence est soulignée dans de nombreuses branches, dont le patrimoine populaire, la soufisme et le roman, en abordant les conditions principales, puis en les appliquant au roman "Antichristos" d'Ahmed Khaled mostapha, mettant en évidence les manifestations de l'étrangeté, de son titre aux personnages, en passant par le temps et le lieu, jusqu'à la langue
Keywords: Wonderful/ Strange/ Supernatural/ Fantastic/ Fantasy; العجيب/الغريب/الخارق /الفانتاستيك /الفانطازيا; Merveilleux / étrange / surnaturel / fantastique / fantasy.